Pragmatism, Rights, and Democracy - Singer, Beth J. (Fordham University Press, 2019)
"Singer's theory of rights, an impressive development of social accounts by pragmatists George Herbert Mead and John Dewey, was developed in Operative Rights (1993). This successor volume includes applications, lectures, replies to critics, and clarifications. For Singer, Dewey, and Mead, rights exist only if they are embedded in the operative practices of a community. People have a right in a community if their claim is acknowledged, and if they would acknowledge similar claims by others. Singer's account contrasts with theories of natural rights, which state that humans have rights by virtue of being human. Singer's account also differs from Kantian attempts to derive rights from the necessary conditions of rationality. While denying that rights exist independently of a community's practices, Singer maintains that rights to personal autonomy and authority ought to exist in all communities. Group rights, an anathema among individualistic theories, are from Singer's pragmatist perspective a valuable institution. Singer's discussion of rights appropriate for minority communities (e.g., the Bosnian Muslims and the Canadian Quebecois) is particularly illuminating. Her book is a model of careful reasoning. General libraries, and certainly academic libraries, should have Singer's Operative Rights. The volume under review is a good addition for research libraries and recommended for graduate students and above."[Singer] examines the views of Rousseau, Mill, and T. H. Green on human rights and those of Dewey and G. H. Mead on the relationship between rights and the democratic process...Recommended."--Choice